Validity and reliability of the Depression Information Needs Scale among the Iranian general population - Jafari, Alireza; Naddafi, Fatemehzahra; Nejatian, Mahbobeh; Charoghchian Khorasani, Elham; Tehrani, Hadi (Frontiers in Psychiatry, 2024)
Introduction: The prevalence of depression in the community is high. Therefore, it is necessary to examine the needs for information on depression in the community. This cross-sectional study aimed to translate and evaluate the psychometric properties of the Depression Information Needs Scale (DINS) among the general population. Methods The translation and assessment of validity and reliability of DINS were conducted from February 2022 to May 2023 in Gonabad, Iran.The inclusion criteria in this study were: Being 18 years or older, living in Gonabad for one year or more, and providing written informed consent. A sample size of 546 was used for EFA (exploratory factor analysis) and 629 was used for CFA (confirmatory factor analysis). The reliability of the DINS was examined using three methods: McDonald’s omega coefficient, test-retest reliability, and Cronbach’s alpha coefficients. Results: Most participants were female, had a bachelor’s degree, and were married. The values of 0.959 for scale content validity index averaging (S-CVI/ Ave) and 0.817 for content validity ratio (CVR) were calculated. In the EFA section, four factors with eigenvalues greater than 1 were extracted and explained 63.861 % of the variance. Only two items were not placed in related or acceptable components and were deleted. Finally, based on the results of goodness-of-fit indexes (for example: RMSEA=0.074, CFI= 0.944, NFI= 0.930, and GFI= 0.911), the scale was approved with 18 items and four factors: lived experience (4 items), General facts about depression (6 items), Research and policies (4 items), and Specific treatments (4 items). For all DINS items, the McDonald omega coefficient, Cronbach’s alpha coefficient, and ICC were 0.953, 0.950, and 0.957, respectively. Conclusion: The Persian version of the DINS was validated with 18 items and four factors, and this scale can be used to assess depression information needs in the general public and specific groups.